The Effectiveness of Religious Influence in Electoral Participation - Septiana, Lia Nadella; Wardana, Dodi Jaya (IHSA Institute, 2024)
Following the general election in Indonesia, various groups engaged in this democratic process with the objective of identifying a leader capable of guiding the nation and its citizens toward the attainment of justice and prosperity. This study will elucidate the various factors influence their participation in this election, with a particular focus on the impact of religion. The effectiveness of religion in electoral processes is a subject of considerable analysis. Nonetheless, it may yield both beneficial and detrimental effects in the context of elections. The beneficial outcomes comprise enhanced inter-group tolerance, whereas the detrimental aspects involve suspicion, conflict, and division. Nonetheless, the research posits that the impact of religion, regardless of its form or extent, will not adversely influence the electoral process provided it remains in alignment with constitutional principles